2005
DOI: 10.1038/sj.eye.6701883
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results from the use of the novel Interactive Binocular Treatment (I-BiT™) system, in the treatment of strabismic and anisometropic amblyopia

Abstract: Improvements in vision were demonstrable within a short period of time, in some children after 1 h of treatment. This system is an exciting and promising application of VR technology as a new treatment for amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 9 publications
(10 reference statements)
3
58
0
Order By: Relevance
“…21 Seven of 12 children (58%) achieved sustained improvements in high-and low-contrast VA in response to treatment using the I-BiT system, and for two children (17%; both with mixed amblyopia), amblyopia was eliminated. Although VA changes were modest, they occurred for a group of children for whom conventional treatment had failed and who were outwith the optimal period of visual plasticity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…21 Seven of 12 children (58%) achieved sustained improvements in high-and low-contrast VA in response to treatment using the I-BiT system, and for two children (17%; both with mixed amblyopia), amblyopia was eliminated. Although VA changes were modest, they occurred for a group of children for whom conventional treatment had failed and who were outwith the optimal period of visual plasticity.…”
Section: Discussionmentioning
confidence: 92%
“…A computer-based virtual reality system (interactive binocular treatment (I-BiT) system) has been developed by a multidisciplinary group from the Queens Medical Centre in Nottingham and the University of Nottingham, 20 and piloted on amblyopes in both Nottingham 21 and Glasgow. The results for the Glasgow Pilot Study are reported here.…”
Section: Introductionmentioning
confidence: 99%
“…This study found a positive effect of I-BiT treatment on VA, of a magnitude similar to I-BiT systems used in previous studies. 10 Early I-BiT prototypes were not user-friendly for children and the equipment was too large to be accommodated in the normal clinical environment. This small study has demonstrated that commercially available 3D shutter glasses can be adapted using specialist software to provide effective amblyopia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Computer games and video footage were displayed in such a way that the amblyopic eye of a patient could be preferentially stimulated during binocular viewing conditions. Visual acuity (VA) gains were demonstrated with prototype systems using different display devices including the 'Cyberscope' desk viewer system (results reported in the study by Waddingham et al 10 ) and the 'Cy-visor' system (results reported in the study by Cleary et al 11 ). This paper reports early results from use of commercially available 3D shutter glasses with bespoke I-BiT game-based software and video presentation.…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed virtual-reality-based display system aims at the treatment of amblyopia by stimulating both eyes simultaneously, using interactive three-dimensional games and videos which are shown to the patient via a stereo display (Eastgate et al 2005). Preliminary results with this system from a group of six children aged 5 to 7 years demonstrated an improvement in acuity in five children after just a few hours of treatment (Waddingham et al 2005). Approaches such as this will have a far better acceptance among children, but the case study results will have to be followed up by a controlled trial to establish their significance and to assess whether binocular function is also improved.…”
Section: The Present and Potential Future Impact Of Work On Animal Momentioning
confidence: 99%